Determining Number of Withdrawal Kanban Using Bi-Level Optimization and Simulation Approaches - Baradaran, Vahid; Akhavan, Behnaz (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Withdrawal Kanban system, by capability of data transferring in supply chain reduces different types of the wastes such as inventories level and unnecessary movements. To achieve the aims of lean production, the parameters of the Kanban system such as the number of Kanban should be determined accurately. The number of Kanban problem is a bi-level optimization problem, because manufacturer and suppliers have different and in competition objectives and decision variables. In this paper, the objectives and constraints of withdrawal Kanban problem has been determined based on a case study in automobile industry supply chain. A mathematical bi-level optimization model with non-linear objectives has been developed and A Genetic Algorithm model for solving is proposed. Also, a simulation model is developed to check the possibility, feasibility and validity of solutions. The simulation studies show one of the feasible solutions can reduce up to 16 percent the transportation costs.